Amygdala responses to quetiapine XR and citalopram treatment in major depression: the role of 5‐HTTLPR‐S/Lg polymorphisms. (16th February 2016) - Ramasubbu, Rajamannar; Burgess, Ashley; Gaxiola‐Valdez, Ismael; Cortese, Filomeno; Clark, Darren; Kemp, Anne; Goodyear, Bradley; Macqueen, Glenda; Bech‐Hansen, N. Torben; Foster, Jane; Diwadkar, Vaibhav A.
Abstract : Objectives: Genotype and drug pharmacology may contribute to variations in brain response to antidepressants. We examined the impact of two antidepressants with differential actions on serotonin transporter and the 5‐HHTLPR‐S/Lg polymorphisms on amygdala responses in major depressive disorder (MDD). Methods: Caucasians with MDD were given either citalopram or quetiapine extended release for 8 weeks. Patients were genotyped for 5‐HTTLPR. Clinical efficacy was assessed using the Hamilton Depression Rating Scale. fMRI responses to negative emotional faces were acquired at baseline, week 1 and week 8. The outcome measure was change in amygdala responses at week 8. Results: Citalopram had no effect on amygdala responses in MDD patients with S/Lg alleles at weeks 1 and 8 compared with baseline, whereas it induced changes in amygdala responses in LL homozygotes. By contrast, quetiapine decreased amygdala responses at both time points in S/Lg carriers, and changes in amygdala responses at week 8 correlated with a reduction in depression scores. The small number of LL homozygotes in quetiapine group was a limitation. Efficacy of both treatments was comparable. Conclusions: These preliminary data suggest that pharmacological mechanisms and genetics need to be considered in the development of neuroimaging markers for the evaluation of antidepressant treatments. Copyright © 2016 John Wiley & Sons, Ltd.